Ultrasmall Au and Ag Nanoclusters for Biomedical Applications: A Review - Tang, Jia; Shi, Haihong; Ma, Guanyu; Luo, Liangping; Tang, Zhenghua (Frontiers in Bioengineering and Biotechnology, 2020)
Noble metal (e. g. Au, Ag, Pt, Pd and alloy) nanoclusters (NCs) have emerged as a new type of functional nanomaterials in nanoscience and nanotechnology. Owing to their unique properties such as ultrasmall dimension, enhanced photoluminescence, low toxicity and excellent bio-compatibility, noble metal NCs especially Au and Ag NCs have found various applications in biomedical regime. This review summarizes the recent advances of employing ultrasmall Au and Ag NCs for biomedical applications, with particular elaboration on bioimaging and biosensing, anti-microbial applications, as well as tumor targeting and cancer treatment. The challenges including the shared and specific challenges for Au and Ag NC toward biomedical applications as well as the outlooks mainly the future research directions are briefly discussed in the end.